Exploitation of tannins to modulate rumen ecosystem and ruminants performance: A review - KUMAR, KAUSHALENDRA; CHAUDHARY, L C; KUMAR, SANJAY (The Indian Journal of Animal Sciences, 2014)
Tannins are polyphenolic polymers of relatively high molecular weight with the capacity to form complexes mainly with proteins due to the presence of a large number of phenolic hydroxyl groups. They are widely distributed in nutritionally important forage trees, shrubs and legumes, cereals and grains, which are considered as anti-nutritional compounds due to their adverse effects on intake and animal performance. However, tannins modulate rumen fermentation favorably such as reducing protein degradation in the rumen, prevention of bloat, inhibition of methanogenesis and increasing conjugated linoleic acid concentrations in ruminant-derived foods. The inclusion of tannins in diets has been shown to improve body weight and wool growth, milk yields and reproductive performance. This review discusses the effects of tannins on nutrient metabolism, rumen fermentation, and microbial populations bacteria, protozoa, fungi and archaea), metabolism of tannins, microbial tolerance mechanisms to tannins, inhibition of methanogenesis, and performance of animals. This review seeks to highlight the practical significance of tannins on ruminant nutrition in developing countries. It will also review approaches to counter the negative effects of tannins.